For Future Teachers in The Process of Globalization Factors for The Development of Ideological Immunity - Joldasbayev Oralbay Ernazarovich (Zien Journals, 2021)
This article focuses on the issues of ideology, ideological immunity, spirituality, spiritual threat in the process of globalization, their causes, content, relevance, problems, tasks, and ways to overcome them the word goes.
Keywords: ideology; immunity; globalization; education